The roles and practices of professional school counselors in inclusive education - Akhmad Sugianto; Amka; Agus Pratomo Andi Widodo; Fairus Niratama; Yuli Yanti (Journal of Professional Teacher Education, 2026)
School counselors help all students, including those with special needs, grow and develop as much as they can.  School counselors face difficulties in implementing inclusive guidance and counseling practices because they lack sufficient knowledge or understanding of the roles and responsibilities of inclusive school counselors. This situation impacts how guidance and counseling services are planned and improved for every student. This study looks at what school counselors do in schools when they work with everyone, including all students. This study employed a qualitative research design. The group included nine people from three different senior high schools located in Hulu Sungai Tengah Regency, Indonesia. Data were gathered using interviews, observations, and written records. The findings revealed that the roles of inclusive school counselors include: (a) identifying students with special needs through needs assessment procedures; (b) Creating programs to help students with special needs reach their full potential; (c) implementing guidance and counseling programs or services for students with special needs; (d) collaborating with various stakeholders within the framework of inclusive education; and (e) conducting continuous evaluations of guidance and counseling programs in inclusive educational settings. Based on these findings, the roles of inclusive school counselors have been implemented in accordance with the key aspects identified in this study to optimize service delivery for all students. The findings imply that schools should provide continuous professional development and strengthen collaboration among school counselors, teachers, parents, and other stakeholders to enhance counselors’ competencies and improve the quality and effectiveness of inclusive guidance and counseling services in addressing the diverse needs of all students.